PtrA regulates prodigiosin synthesis and biological functions in Serratia marcescens FZSF02 - Lin, Junjie; Yu, Yanshuang; Zhao, Ke; Zhao, Jie; Rensing, Christopher; Chen, Jichen; Jia, Xianbo (Frontiers in Microbiology, 2023)
Serratia marcescens is a gram-negative bacterium that is able to produce many secondary metabolites, such as the prominent red pigment prodigiosin (PG). In this work, a ptrA-disrupted mutant strain with reduced PG production was selected from Tn5 transposon mutants. RT-qPCR results indicated that ptrA promoted elevated transcription of the pig gene cluster in S. marcescens FZSF02. Furthermore, we found that ptrA also controls several other important biological functions of S. marcescens, including swimming and swarming motilities, biofilm formation, hemolytic activity, and stress tolerance. In conclusion, this study demonstrates that ptrA is a PG synthesis-promoting factor in S. marcescens and provides a brief understanding of the regulatory mechanism of ptrA in S. marcescens cell motility and hemolytic activity.